Strategi Pengembangan Digital Marketing dan Personal Selling Halal Food di Kopi Telu Sawah View Pandaan Pasuruan - Ruhbatul A’fiah Diah Ayu Ningtyas; Muhammad Fahmul Iltiham; Sukamto; Muhammad Nizar (Alkasb: Journal of Islamic Economics, 2022)
In the working environment, the use of technology today is very beneficial for marketing activities. Companies can sell goods and services through a variety of platforms with good technology. Marketing campaigns use digital technology, or "digital marketing". This research aims to determine the development strategy of digital marketing and personal selling of halal food in Kopi Telu Sawah. View Pandaan Pasuruan and the supportive and inhibiting factors of the strategy of development of digital Marketing and personal sales of halal food at Kopi Telu Sawah. The type of research that researchers use is qualitative research using descriptive approaches. The research tools used by the researchers in this study are observations, interviews, and documentation. From the results of this research, it is explained that the strategy implemented for the development of the halal food business in Coffee Telu is to provide a good service, maintain the quality of products, use social media, and cooperate with influencers. This provides a great opportunity to attract consumers to visit and enjoy the products and facilities provided.